Feasibility and performance of high-rate psychrophilic dry anaerobic digestion of high solids content dairy manure - Noori M. Cata Saady; Daniel I. MassÃ© (International Journal of Recycling of Organic Waste in Agriculture, 2024)
Purposes The main purpose of the R&D was to develop a novel high-rate psychrophilic dry anaerobic digestion (PDAD) for processing a mixture of cow feces and wheat straw (CFWS) in sequencing batch bioreactor (SBR) operated at high organic loading rate (OLR). The main research question was to assess the feasibility of operating the PDAD-SBR at OLR of 9.0 and 10.0 g TCOD kg-1 inoculum day-1 . Methods Two pairs of 40 L duplicate bioreactors located in a temperature-controlled room (20 C) were operated as sequencing batch reactors (SBRs) and were fed CFWS (27 % total solids) at OLRs of 9.0 and 10.0 g TCOD kg-1 inoculum day-1 during three successive treatment cycles of 21 days each. The biogas production, biogas composition, volatile fatty acids, and volatile solids were monitored to assess the performance of the PDAD-SBRs. Results The PDAD process fed with cow feces and wheat straw (TS of 27 %) at OLR 9.0 and 10.0 g TCOD kg-1 inoculum day-1 (6.53 ± 0.06 and 7.27 ± 0.12 g VS kg-1 inoculum day-1 ) resulted in average specific methane yields (SMYs) of 134.0 ± 7.7, 136.4 ± 4.9 NL CH4 kg-1 VS fed, respectively, with an average volatile solids removal of 35 % at the ends of treatment cycles (21 days). Conclusions This study reports for the first time successful operation of psychrophilic (20 C) dry anaerobic digestion (PDAD) of cow feces with wheat straw (CFWS) at 27 % total solids and OLR of 9.0 and 10.0 g TCOD kg-1 inoculum day-1 in relatively short treatment cycle length (21 days).